Soil mechanics and resistance study: Lima case - Gallarday Bocanegra, Tomás (2012)
It is necessary to carry out mechanics and soil resistance studies before deciding to carry out a civil construction with a height greater than 6 meters, in the Lima area, considering that it has a heterogeneous, conglomeradic suleo and is located in an area of ​​seismic risk [10 , 1], for this, a granularity determination will be made, which influences the movement and resistance of the soil, which will support the weight of the superstructure. To obtain its result, it is essential to practice a pit or pit that has width and depth according to the design of the foundation, allowing workers to operate easily. Sporadically when the technical and physical circumstances of the soil allow it, its sampling can be carried out in situ, determining in the field the internal friction angle, which will give the moment of failure for the soil, simulating the pressure exerted by the work, to know this physical data requires the application of Peruvian technical standards, which classify soils for civil engineering purposes, this includes the analysis of the results carried out in prestigious national laboratories, with this information the Data parameter is determined, prior to the application of the terzaghi formula [ 14] that allows conclusions to be drawn that, when applied, avoid unnecessary overload, given by the use of exaggerated material in the foundation of civil works, with a negative impact on costs, taxing the economy of the owners.